INDEKS ENTOMOLOGI VEKTOR DEMAM BERDARAH DENGUE DI TIGA KABUPATEN DI PROVINSI BALI - Wening Widjajanti; Rima Tunjungsari Dyah Ayuningtyas; Ni Wayan Dewi Adnyana (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
Incidence rate Dengue Haemorrhagic Fever (DHF) in Bali Province ranks first in Indonesia in 2011-2015. DHF is caused by dengue virus transmitted by Aedes spp. The risk of DBD transmission is measured by density figure. This research was conducted in Jembrana, Karangasem and Badung Districts of Bali in 2017 with the aim to know the entomology’s index in those districts. Larvae of Aedes spp. collected from 100 homes in each location in the area. The results of mosquito larvae were calculated by indicator of larvae index of House Index (HI), Container Index (CI) and Breateu Index (BI). The result of HI in Jembrana, Karangasem and Badung’s districts are 19%, 27% and 45%. The result of CI in Jembrana, Karangasem and Badung’s districts are 9,25%; 17,37% and 24,41%. The result of BI in Jembrana, Karangasem and Badung’s districts are 25%, 41% dan 62%. The types of mosquito breeding places in Jembrana and Karangasem are mostly found in buckets, while in Badung regency were found in bathtube. The potential for DHF transmission is still ongoing in these three kabupates. The efforts of larvasidation, eradication of mosquito nests and extension should be done by these three districts.